Zakat and Waqf in the Era of Capitalism: Reconstructing the Paradigm of Economic Justice within the Modern Financial System - Ikhsan, Ainul; Luthfi Sartono, Muhammad; Kamil Husain, Muhammad (Asian Journal of Muslim Philanthropy and Citizen Engagement, 2026)
Islamic philanthropic instruments such as zakat and waqf face a profound paradox within the global capitalist system. While embodying ideals of substantive economic justice and community empowerment, in practice they often become subsumed by the dominant economic logic, limiting their transformative potential. This study aims to reconstruct the paradigm of economic justice by critically examining strategic pathways to integrate Islamic philanthropy into modern financial architecture. Employing a qualitative library research approach through in-depth literature study and thematic analysis, the research reveals that the fundamental incompatibility between Islamic philanthropy and capitalism is philosophical and axiological, concerning the very purpose of economic activity. However, this tension can be bridged through innovative models such as stock waqf and productive sukuk, which merge Islamic solidarity ethics with market efficiency. Meaningful integration ultimately requires paradigmatic transformation within the financial system itself, placing principles of distributive justice (al-’adl) and public welfare (maslahah) at its core. Thus, Islamic philanthropy can evolve from traditional charity into an ethical counterbalancing force within global capitalism, offering a viable pathway toward a more inclusive and equitable economic paradigm.